Human resources management practices and approaches in insurance - Faur, Flaviu Casian; Albescu (Sanda), Cristina Maria; Grapini, Ioan (Technium Social Sciences Journal, 2022)
Looking with interest at the moments of recession and crisis before, but also at the pandemic and the current situation related to the political crisis in Ukraine, the geopolitical and economic context we are going through, both Romania and Europe, forces us to change and to adopt new approaches in terms of the whole activity, but especially the one related to the professional activity. The labor crisis, the coronavirus pandemic and the war in Ukraine are further accelerating the process of changing and changing the way organizations work, so human resource management needs to identify new approaches, methods and tools that work well and effectively in close connection with innovation and new technologies. The insurance sector is perhaps the most affected branch of the service area due to the effects of the pandemic and the labor crisis, so the need for new and innovative approaches to human resource management in insurance is imminent and must be treated with great responsibility by managers from this section. These methods and approaches aim to increase work performance and efficiency, increase the quality of work, create a pleasant environment for employees and an encouraging work environment so that the level of satisfaction is at its maximum.